APLIKASI BERITA ACARA PEMERIKSAAN BARANG BERBASIS WEB PADA KPPBC TIPE MADYA PABEAN B SURAKARTA - Dwi Ratna Sari; Dwi Retnoningsih; Firdhaus Hari Saputro Al Haris (JURNAL GAUNG INFORMATIKA, 2019)
The making of investigating report on the factory of tobacco products (cigarette and tobacco factories) in middling KPPBC Pabean B at Surakarta was still done semi-manually with Microsoft Office. Even though an investigating report was computerized but it was still not effective. It is due to the fact that the officers had to manually record of investigation results on the forms and input the data one section at a time in Microsoft Excel. Semi-manual data processing is a problem in completing work. These problems include lag in processing data. The investigating report system on web-based in middling KPPBC Pabean B at Surakarta is used to complete the work in making the investigating report to be faster and more accurate. It is because the large number of supervision and work areas of middling KPPBC Pabean B at Surakarta. This study used the waterfall method as a system design while data collection techniques used interviews, observation, literature studies and questionnaires. Whereas, the system testing used the webqual method. This research produces a system of investigating report on web-based in middling KPPBC Pabean B at Surakarta. System testing shows that usability quality has a positive effect on user satisfaction because it has a significance value of 0.03 0.05 and interaction service quality has a positive effect on user satisfaction because it has a significance value of 0.001